Smart Village Map: Peta Desa Way Huwi Berbasis Web Untuk Pembangunan Berkelanjutan - Welly, Tri Kies; Nadzir, Zulfikar Adlan (TeknoKreatif: Jurnal Pengabdian kepada Masyarakat, 2021)
Village development is a long-term sustainable project. Village development efforts have always been pursued by the government at various periods with various policies, namely in the form of aid funds, internet network development, infrastructure development, and so on. Way Huwi Village is one of the villages in the administrative area of South Lampung Regency near Bandar Lampung city, acts as its ‘satellite’, so it needs an integrated system to maximize potential by dissemination of geospatial information to the villagers. The Community Service aims to meet the need for web-based geospatial information in Way Huwi Village. The method used in data collection by mapping using photogrammetric methods by means of UAV and field surveys to obtain village map information. This community service is used for development planning using the smart village concept effectively and sustainably, as well as increasing awareness of the importance of the availability of geospatial information in community economic improvement activities to improve the standard of living of Way Huwi village.